Urban Restructuring, Homelessness, and Collective Action in Toronto, 1980–2003 - Greene, Jonathan (Urban History Review / Revue d'histoire urbaine, 2014)
This article explores the links between urban restructuring, homelessness, and collective action in Toronto in the 1980s and 1990s. In Toronto, as elsewhere, urban restructuring at this time comprised a series of interconnected political-economic and spatial shifts, including economic and occupation change, gentrification, neo-liberal welfare state reform, and urban entrepreneurialism. Jointly, these political-economic shifts were implicated in the production and consolidation of new forms of socio-spatial polarization and segregation that dramatically changed the landscape of urban poverty. One of the most visible manifestations of the uneven effects of restructuring was the emergence and consolidation of mass homelessness. This changing landscape of poverty, in turn, produced a new landscape of political activism. It is this contested landscape that I explore in this article through a focus on homelessness as a primary mobilizing issue in opposition to restructuring during this key period in Toronto’s transition into a second-tier world city. I argue that urban restructuring, homelessness, and the dynamics of collective action were linked in two important ways. First, collective advocates and activists defined the crisis of homelessness as a direct effect of urban restructuring; in this way collective action mobilized to defend the interests of homeless people was simultaneously a collective struggle to contest urban restructuring. Second, the politics of restructuring directly informed the dynamics of collective action over time, influencing their organizational, strategic, and tactical dimensions.